2002
DOI: 10.1046/j.1440-1681.2002.03748.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual nitric oxide mechanisms of cholestasis‐induced bradycardia in the rat

Abstract: 1. Cholestatic liver disease is associated with nitric oxide (NO) overproduction and bradycardia. Nitric oxide has a dual effect on sinoatrial node and its effects depend on its concentration. Nitric oxide can increase heart rate by activating hyperpolarization-activated pacemaker current (If) but, at high concentrations, it can potentially decrease heart rate by inhibition of L-type calcium current. In the present study, the responsiveness of isolated atria to CsCl (an inhibitor of the If current) and acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 24 publications
6
33
0
Order By: Relevance
“…28 Rats with biliary cirrhosis are bradycardic, 29 and this condition is owing to a significant hyporesponsiveness to the chronotropic effect of catecholamines. 7,8 In the present study, we showed that two independent treatments (N-acetylcysteine and L-NAME), both of which can normalize chronotropic responses to adrenergic stimulation in vitro, also led to normalization of heart rate in vivo (Fig. 2).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…28 Rats with biliary cirrhosis are bradycardic, 29 and this condition is owing to a significant hyporesponsiveness to the chronotropic effect of catecholamines. 7,8 In the present study, we showed that two independent treatments (N-acetylcysteine and L-NAME), both of which can normalize chronotropic responses to adrenergic stimulation in vitro, also led to normalization of heart rate in vivo (Fig. 2).…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, we have shown that increased NO synthesis in bile ductligated (BDL) rats causes bradycardia by causing impaired responsiveness of cardiac pacemaker cells to adrenergic stimuli. 7,8 Nitric oxide is involved in the modulation of cardiac function in the normal heart, as well as in various cardiac diseases via mechanisms involving NO that are both dependent on and independent of guanylyl cy-clase. 9,10 For example, evidence suggests NO attenuates cardiac pacemaker activity, mediated by cyclic guanosine monophosphate (cGMP).…”
mentioning
confidence: 99%
“…It is likely that the timing and level of NO production in the healing wound must be carefully balanced to ensure a beneficial effect. [39][40][41][42] This work also demonstrated that human tendon cells have the capacity to synthesize physiologically active NO following transfection of iNOS gene via adenovirus.…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that cholestatic liver disease is associated with hypotension [1,2], bradycardia [3][4][5], QT prolongation [6], hyporesponsiveness of cardiovascular system to adrenergic stimulation [7][8][9], and tendency to hypovolemic shock and acute renal failure [10][11][12]. QT prolongation usually increases vulnerability to arrhythmia in congenital and acquired conditions [13].…”
Section: Introductionmentioning
confidence: 99%